PENGARUH PELAPISAN FOSFOR PADA UMPAN BUATAN TERHADAP JENIS IKAN PANCING - Ida Ayu Lochana Dewi; Joi Alfredo Surbakti (Politeknik Pertanian Negeri Kupang, 2020)
Artificial bait for fishing rod is the key component for successful catch. Artificial bait is usually designed in certain ways that will attract fish to go after it. One of the design for artificial bait is the addition of phosphor in order to improve the bait’s ability to radiate light so fish will be attracted to go after it. The research is conducted in Kupang Bay, East Nusa Tenggara from April to May 2020. The method used is experimental fishing, with increasing amount of phosphor being used in every 60 grams of bait. There are four levels of treatment; without phosphor, 10 grams, 30 grams, and 50 grams of phosphor. The amount of fishing trips being repeated are 16. Result of the research shows that there are nine type of caught fish, which are Sphyraena sp, Lutjau ruselli, Caranx sexfasciatus, Plectropomus leopardus, Rastrelliger sp, Trichiurus lepturus, Lutjanus lutjanus, Lutjanus jocu, and Epinephelus coioides. The result of analysis of variance shows that increasing amount of phosphor significantly impact the amount of type of fish being caught. Using LSD test, it also shows a significant difference of type of catch between bait without and with phosphor. Based on catching point, there are four spots with overall bait treatment resulting in a catch. Those waters are Tenau, Kera, and Semau.